DEVELOPED MODEL OF STEEL RESTRAINED ELEMENTS DESIGN FOR STABILITY BY THE COMPATIBLE ACTION OF TRANSVERSE BENDING AND TORSION (Collection of scientific works «Modern structures of metal and wood», 2020)
The main stages of the calculation of steel restrained flexible elements with initial imperfections  are  considered  according  to  the  deformed  scheme.  Restraint  can  occur  using structures attached to the steel beam, such as profiled flooring, which is attached with self-tapping screws. The goal to find and describe the features of beam operation under the combined action of transverse bending and torsion was set on the basis of a new approach to the analysis of internal force factors. The existing theoretical model has been improved to eliminate the deficiencies present in  it.  A comparison of the  methods  for determining the  bearing  capacity of  flexible elements  by stability was carried out using examples. It was proposed to increase material savings by detailing the calculation. The moments to which you need to pay attention when calculating the restrained elements, especially the purlins of a light inclined roof, were highlighted to match the constructed model with the real work of beams with complex resistance. The complexity of the mathematical description of the bending-torsional bimoment function often leads to simplifications and analytical errors in the process of determining the  internal  forces, which depend on the function of the rod angle  of  rotation.  Therefore,  it  was  decided  to  clarify  the  model  for  determining  the  bearing capacity of restrained steel elements of various cross-sections. The tasks of identifying the causes and consequences of the occurrence of torsion, studying methods of control or minimization require further  theoretical  research  and  solutions.  It  is  proved  that the  calculated  bimoment  depends  not only on the load, its eccentricity, the elastic bending-torsional constant of the cross-section and span of the beam, but also on the stiffness of the structures laterally attached to the beam. The optimal cross-sectional shape of the rolled purlin for an inclined roof was justified, namely the I-beam, due to a decrease in the negative effect of the torsion load.